IOT Based Monitoring of Household Electricity Appliances - Sri lakshmi, M; Sairam, P; Yeswanth, V; Akhila, P (International Journal of Engineering and Technology, 2018)
A Smart Electricity meter is a new kind of electricity meter that can send meter reading and billing to the user. They are a replacement for standard meters, which use technology created decades ago .Smart electricity meters have been in development in many countries. Presently, people have to come to electricity meter to generate bill. We could not know how many units of current we have been consuming from time to time. The system we propose in this paper is a smart electricity meter which will monitor the current electricity usage and gives a notification to us which says how many units of current have been consumed and the amount we have to pay. we can also enable a setting that will notify us whenever particular units of current have been consumed. The entire consumption history of current from time to time can be monitored in the database. Â Â